Strengthening sociopreneurship culture through the Pentahelix collaboration model - Gugus Wijonarko (International Journal on Social Science, Economics and Art, 2023)
Sociopreneurship is a social movement solution in the economic sector that can provide business opportunities that can ultimately improve the community and national economy. Apart from being sustainable, sociopreneurship can provide effective and tactical solutions to the economic problems of society. Especially in the post-COVID-19 pandemic situation in Indonesia, the sociopreneurship approach can be an alternative to accelerate community economic recovery. However, the development of socio-preneurship in Indonesia is considered to be still relatively behind compared to other countries. For this reason, this research aims to explore more deeply what factors hinder the development of sociopreneurship in Indonesia and what strategies to improve it. The research method uses a qualitative approach with a descriptive research type. Data collection through in-depth interviews and documentation. Interviews were conducted with sociopreneurship actors in Surabaya. The research results show several obstacles, including a lack of public understanding of the importance of building social entrepreneurship, the still dominant traditional business culture, and limited access to capital and networks. For this reason, collaboration between various parties is needed through the pentahelix model so that the culture of sociopreneurship can continue to grow and become stronger